2019
DOI: 10.1016/j.ast.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Mode multigrid - A novel convergence acceleration method

Abstract: This paper proposes a mode multigrid (MMG) method, and applies it to accelerate the convergence of the steady state flow on unstructured grids. The dynamic mode decomposition (DMD) technique is used to analyze the convergence process of steady flow field according to the solution vectors from the previous time steps. Unlike the traditional multigrid method, we project the flowfield solutions from the physical space into the modal space, and truncate all the high-frequency modes but only the first-order mode ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Instead of the initial guess, Andersson [410] adopted DMD in intermediate iterations to correct the solution closer to a steady-state condition and thus accelerated the convergence of steady flow simulations. Liu et al [411] proposed a mode multigrid method using DMD to truncate all the high-frequency parts in steady flow simulations and achieved speedup ratios of 3 to 6 while ensuring the computational accuracy, and Chen et al [412] used a similar strategy to accelerate the convergence of the steady adjoint equations. Liu et al [413] improved the efficiency of implicit dual time scheme for unsteady flow simulations by providing proper initial solutions using DMD at each physical time step.…”
Section: Numerical Simulation Accelerationmentioning
confidence: 99%
“…Instead of the initial guess, Andersson [410] adopted DMD in intermediate iterations to correct the solution closer to a steady-state condition and thus accelerated the convergence of steady flow simulations. Liu et al [411] proposed a mode multigrid method using DMD to truncate all the high-frequency parts in steady flow simulations and achieved speedup ratios of 3 to 6 while ensuring the computational accuracy, and Chen et al [412] used a similar strategy to accelerate the convergence of the steady adjoint equations. Liu et al [413] improved the efficiency of implicit dual time scheme for unsteady flow simulations by providing proper initial solutions using DMD at each physical time step.…”
Section: Numerical Simulation Accelerationmentioning
confidence: 99%
“…ey applied the presented method to the Hodge-Helmholtz decomposition test case and showed better accuracy related to second-order discretization. In 2019, Liu et al [23] proposed a mode multigrid method and applied it to a steady-state solver for unstructured grids. ey used the solver for 2D and 3D foils and showed that the method is 3 to 6 times faster than the baseline method while ensuring computational accuracy.…”
Section: Introductionmentioning
confidence: 99%